1999
DOI: 10.1136/jcp.52.6.455
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a subtype of colorectal cancer combining features of the suppressor and mild mutator pathways

Abstract: Background-10% of sporadic colorectal cancers are characterised by a low level of microsatellite instability (MSI-L). These are not thought to diVer substantially from microsatellite-stable (MSS) cancers, but MSI-L and MSS cancers are distinguished clinicopathologically and in their spectrum of genetic alterations from cancers showing high level microsatellite instability (MSI-H). Aims-To study the distribution of molecular alterations in a series of colorectal cancers stratified by DNA microsatellite instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
165
1
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(183 citation statements)
references
References 37 publications
(47 reference statements)
10
165
1
5
Order By: Relevance
“…Most high-MSI tumors are admixed hyperplastic and adenomatous polyps rather than serrated polyps. 3,4,8,11,14,15 In our study, the right colon showed a higher percentage of methylation and more frequent methylation of the p16, p14, TIMP3, and FHIT genes than the left colon. These results are comparable with the results reported by Burri et al 25 using colonic carcinoma samples.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Most high-MSI tumors are admixed hyperplastic and adenomatous polyps rather than serrated polyps. 3,4,8,11,14,15 In our study, the right colon showed a higher percentage of methylation and more frequent methylation of the p16, p14, TIMP3, and FHIT genes than the left colon. These results are comparable with the results reported by Burri et al 25 using colonic carcinoma samples.…”
Section: Discussionsupporting
confidence: 50%
“…6 The polyps of this pathway differ morphologically and genetically from those of the traditional adenoma-carcinoma sequence. 7 Genetically, serrated adenomas are differentiated from sporadic tubular adenomas by a high frequency of the low mutator phenotype, 3,8 p53 mutations, 9 KRAS mutations, 9,10 BRAF mutations, 11 and a low frequency of APC gene mutations. 12 However, the prevalence of the high mutator phenotype and its significance during tumorigenesis are controversial and the chromosomal status of serrated adenoma has not been studied.…”
mentioning
confidence: 99%
“…This finding leads to the hypothesis that pERK is involved in the mechanism of tumor progression of MMR-proficient CRC and Lynch syndrome by interacting with the wnt signaling pathway and RHAMM: (1) KRAS mutation is found in approximately 35% of unselected CRCs, whereas it is mutated at a particularly low frequency in sporadic MSI-H cancers. [38][39][40][41][42] (2) The molecule ERK, a member of the MAPK pathway, is activated by a cascade of phophorylation events downstream from the ras proto-oncogene. 8 (3) Intracellular and cell surface RHAMM isoforms are important for the activation of ERK by PDGF (platelet-derived growth factor) and mutant (activated) RAS, respectively, while intracellular RHAMMv4 overexpression activates ERK.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MSS/MSI-L tumors, in contrast to MSI-H tumors, occur most commonly in the left colon and rectum and harbor k-ras, APC, and p53 mutations more frequently, and exhibit silencing of the DNA repair gene O-6-methylguanine DNA methyltransferase (O 6 -MGMT) through promoter methylation. 10,11 MSI-H tumors are predominantly located in the proximal colon and are often characterized histologically by poor differentiation, lymphocytic infiltration and extracellular mucin production. Both MSI-H and MSS/MSI-L tumors appear to arise from hyperplastic polyps evolving to serrated adenomas.…”
Section: B I O S C I E N C E N O T F O R D I S T R I B U T I O Nmentioning
confidence: 99%